Hunian Minimalis RumaRB: dari Tampilan ke Reduksi untuk Efisiensi - Bramasta Putra Redyantanu (Arsir: Jurnal Arsitektur, 2025)
This paper aims to reflect on the concept of minimalism as a design method and philosophy, far beyond the mere minimalist visual appearance commonly understood. This understanding responds to the trends in home design in Indonesia, where minimalism is often perceived as a design that emphasizes visual simplicity. However, the greatest potential of minimalism in modern architecture lies in the effort to simplify spatial design processes and methods with a reductive approach. This qualitative case study highlights the design of a simple residential house using the reduction approach. The connection between reduction and minimalism is reflected in various architectural design aspects, including reduction in building capacity, materiality, and design identity. The findings of this study propose the concept of reduction as a method closely related to various efficiency efforts. The ultimate goal is to expand the understanding of minimalism not merely as an aesthetic but as a reduction-based approach towards various aspects of sustainability in design.